Speaking in bones [compact disc, unabridged] : a novel - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2015)
Forensic anthropologist Temperance Brennan investigates what looks to be a typical missing person case, only to find herself digging up bones possibly left by a serial killer, a cult, or perhaps something not entirely of this world.